Globular cluster systems in low-luminosity early-type galaxies near the Fornax cluster centre - Bassino, Lilia Patricia (2006)
We present a photometric study of the globular cluster systems (GCSs) of the Fornax cluster galaxies NGC 1374, NGC 1379 and NGC 1387. The data consist of images from the wide-field MOSAIC imager of the Cerro Tololo Inter-American Observatory (CTIO) 4-m telescope, obtained with Washington C and Kron-Cousins R filters. The images cover a field of 36 × 36 arcmin2, corresponding to 200 × 200 kpc2 at the Fornax distance. Two of the galaxies, NGC 1374 and NGC 1379, are low-luminosity ellipticals while NGC 1387 is a low-luminosity lenticular. Their cluster systems are still embedded in the cluster system of NGC 1399. Therefore, the use of a large field is crucial and some differences to previous work can be explained by this. The colour distributions of all GCSs are bimodal. NGC 1387 presents a particularly distinct separation between red and blue clusters and an overproportionally large population of red clusters. The radial distribution is different for blue and red clusters, red clusters being more concentrated towards the respective galaxies. The different colour and radial distributions point to the existence of two globular cluster subpopulations in these galaxies. Specific frequencies are in the range SN = 1.4-2.4, smaller than the typical values for elliptical galaxies. These galaxies might have suffered tidal stripping of blue globular clusters by NGC 1399.